Perception of Lifestyle Modification Recommendations among Type 2 Diabetes Patients attending at a Tertiary Level Hospital, Kathmandu - Pandey, Apsara (Journal of Nursing Education of Nepal, 2023)
Prevalence of Type 2 diabetes Mellitus (DM) is increasing globally. The objective of this study was to identify perception of life style modification recommendations among type 2 diabetes mellitus patients attending at diabetes clinic at Tribhuvan University Teaching Hospital, Kathmandu, Nepal. Methods: Descriptive cross-sectional study design was adopted and involved 104 diabetes patients using non- probability purposive sampling technique. Data were collected through an interview by using a structured interview schedule. Findings: Data were analyzed using SPSS version 16.0. Among the respondents, 29.8% were of 50-59 years age group, 51.0% were female, 63.5% were Brahman/Kshetri, 22.1% were illiterate, 89.4% were married, and 50% lived in a nuclear family and 73.1% were from Kathmandu Valley. Forty four percent were diagnosed for 1-5 years and 43.3 % had family history of diabetes, 70.19% respondents perceived that both regular exercise and planned and controlled diet were as important lifestyle modification to control type 2 diabetes mellitus; and 41.3% respondents felt exercise as potentially exacerbated illness. Similarly, 52.8% respondents perceived that DM patients should eat low carbohydrate, high fiber, and low fat and low calorie diet (89.02 %). More than half of the respondents perceived that cessation of alcohol and smoking is important for DM patients. Maintaining a modified lifestyle is time consuming and a difficult task (61.0%) for them. In conclusion, Perception of lifestyle modification such as planned and controlled diet and exercise play an important role in the management of patients with type 2 DM. However, significant numbers of respondents had perceived that exercise as potentially exacerbating illness. So, proper counseling is recommended to combat such perception.